Perancangan Robot Pemindah Balok dengan Menggunakan Wireless Berbasis Mikrokontroler AtMega 128 - Saleh Yaakub (Jurnal INOVATOR, 2019)
his robot is designed to move beams correspond to the given instructions. It is made of wireless controlling devices. They are aimed to control any robot’s movements, and robots by themselves can work and move beams. These control devices are installed used both signal frequency with the appropriate control distance and wireless capability connected through microcontrollers. Users in this case can comprehensively alter the way robot works through this provided controlling devices